Two types of composite phase change panels containing a ternary hydrated salt mixture for use in building envelope and ventilation system. (1st December 2018) - Sun, Wanchun; Huang, Rui; Ling, Ziye; Fang, Xiaoming; Zhang, Zhengguo
Highlights: Co-integration of two composite phase change materials in building was explored. A CaCl2 ·6H2 O-NH4 Cl-SrCl2 ·6H2 O mixture was developed to prepare composites. The composites were based on two matrices with different thermal conductivities. A test room composed of a main room and a ventilation system was constructed. The test room containing two types of composite panels has better thermal comfort. Abstract: Herein the co-integration of two composite phase change materials into building envelopes and ventilation systems was first explored for reducing indoor temperature fluctuation. Specifically, a ternary mixture consisting CaCl2 ·6H2 O, NH4 Cl and SrCl2 ·6H2 O was combined with expanded perlite and expanded graphite to prepare two composites with different thermal conductivities, followed by fabricating them into two kinds of panels. A test room composed of a main room and a ventilation system was constructed, in which the expanded perlite-based composite panels were placed at the insides of the four walls, floor and roof of the main room, while the other expanded graphite-based composite ones were incorporated into the ventilation system. It is shown that the ternary mixture consisting of 95 wt% CaCl2 ·6H2 O-4 wt% NH4 Cl-1 wt% SrCl2 ·6H2 O exhibits a melting point of 23.46 °C, lower than that of CaCl2 ·6H2 O, making it more suitable for use in buildings. Its melting enthalpy is as high as 173.2 kJ/kg. The thermal conductivities of the expanded perlite- and expanded graphite-based composites have been measured to be 0.1170 and 9.720 W/(m·K), respectively. Compared with the room equipped with the expanded perlite-based composite panels at the envelopes, the one containing the two composite phase change panels at the envelopes and the ventilation system simultaneously exhibits a reduced indoor temperature fluctuation (22.29–28.69 °C) and a higher frequency of thermal comfort (78.3%). This work paves the way to the exploitation of hydrated salts as well as the applications of the phase change composites with different thermal conductivity in buildings envelopes and ventilation systems.